ATTEMPTS OF THE AGRARIAN REFORM AT THE BEGINNING OF THE XX CENTURY, OR OPPOSITION OF THE MINISTRY OF INTERNAL AFFAIRS AND THE MINISTRY OF FINANCE IN SOLVING THE PEASANT QUESTION - I. Shcherbakova (Вестник университета)
An attempt to solve the agrarian question at the beginning of the 20th century has been analyzed. The interaction and confrontation of two ministries – the Ministry of Finance and the Ministry of the Interior and local authorities: local committees of the Special Meeting on the needs of the agricultural industry and provincial committees of the Editorial Commission of the Ministry of the Interior, their attempts to discuss and resolve the peasant issue at the beginning of the 20th century, – have been examined. It has been substantiated, that at the beginning of the 20th century the state authorities did not develop a unified course in resolving the peasant issue and only the events of the 1905 revolution forced the government to take emergency measures in the development of agricultural legislation.